Practical aspects of the introduction of innovative technologies in banks - E. V. Pushniak; A. V. Salnikov (Путеводитель предпринимателя)
This scientific article presents a study of the directions of the introduction of innovative technologies in the banking sector. The authors consider innovative technologies used in banks, give examples of successful implementation of these technologies in world practice and in the Russian market, such as the introduction of digital customer service channels, online banking, the use of artificial intelligence and machine learning, the introduction of blockchain technologies and others. The article also contains an analysis of the advantages and risks of introducing innovative technologies, as well as provides recommendations for their successful implementation. In addition, the authors present the prospects for the development of the banking sector in the context of the use of innovative technologies. The article suggests aspects of the introduction of innovative technologies that are of practical interest to banks, managers and researchers who are interested in the application of innovative technologies in banks.